IDENTIFIKASI RHODAMIN B DALAM SAUS SAMBAL YANG BEREDAR DI KOTA PEKALONGAN - Siska Rusmalina; Metha Anung Anindhita (LPPM Universitas Pekalongan, 2015)
Rhodamine B is prohibited additive used on foods. If these compound into the body, can lead to damage to the liver, kidney, spleen and anatomical changes in organs. However, this compound is found in many foods that are red as chili sauce. To protect the public from abuse of these compounds, the study of Rhodamine B in chili sauce sold in the traditional market needs to be done. This research is descriptive qualitative. The location was used in this study is mains three traditional markets in the city of Pekalongan with a total of samples chilli sauce is eight. Rhodamine B in chili sauce detected by linking the coumpoud on the wool yarn, then washed with water flowing. Chili sause samples tasted positive for Rhodamine B, if the analyte bound to the wool yarn can not be leached by water flowing. The result of this research was eight samples of the chili sauce does not contain dye Rhodamine B. As evidenced by the color of analyte Rhodamine B on wool yarn can be washed by water.